2006
DOI: 10.1007/s00420-006-0113-8
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of musculoskeletal pain among female kitchen workers

Abstract: Widespread co-occurrence of musculoskeletal pain symptoms was common among female kitchen workers with slight predominance in the upper body.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
68
3
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(104 citation statements)
references
References 32 publications
26
68
3
7
Order By: Relevance
“…In the Finnish public sector, kitchen workers are among the three occupations with the highest rates of SA (15). We have previously found that multisite pain among female municipal kitchen workers is common (16). In the current work among this occupational group, our aim was to study to what extent multisite pain and musculoskeletal diseases, as well as other somatic diseases, depressive symptoms, physical and psychosocial workload, and health-related lifestyle factors are predictive of the course of SA related to musculoskeletal pain during a two-year follow-up.…”
mentioning
confidence: 94%
“…In the Finnish public sector, kitchen workers are among the three occupations with the highest rates of SA (15). We have previously found that multisite pain among female municipal kitchen workers is common (16). In the current work among this occupational group, our aim was to study to what extent multisite pain and musculoskeletal diseases, as well as other somatic diseases, depressive symptoms, physical and psychosocial workload, and health-related lifestyle factors are predictive of the course of SA related to musculoskeletal pain during a two-year follow-up.…”
mentioning
confidence: 94%
“…In addition to burn and cut injuries, low back pain (LBP) is prevalent in these working populations found in previous studies [5][6][7][8] . LBP is the most frequent cause of disability compensation, accounting for a very large portion of workers' compensation cost in industrialized countries [9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported to involve a heavy workload and carry risks of musculoskeletal disorders [5][6][7][8] . Kitchen workers are also reported to be one of the highest risk occupational groups for workrelated injuries because of the nature of their work and the types of materials handled 14,15,26,27) .…”
Section: Introductionmentioning
confidence: 99%
“…Nesses estudos verificou-se ainda que fatores como ambiente de trabalho, espaço físico, equipamentos, organização e fatores psicossociais do trabalho geram repercussões na saúde dos trabalhadores 3,5,6,8 . O mesmo foi observado em outros países, em pesquisas realizadas em cozinhas de hotéis e restaurantes [9][10][11] .…”
Section: N T R O D U ç ã Ounclassified
“…Estudos realizados no Brasil e no exterior com trabalhadores de cozinhas industriais e hotéis relatam também altas prevalências de sintomas nos membros inferiores 5,24 , nos ombros 5,10,11 e na região lombar [9][10][11] .…”
Section: I S C U S S ã Ounclassified